Tantangan di Balik Kesuksesan: Kisah Perjalanan Pak Jailani dalam Memulai UMKM “Bandrek Pak Kumis” - Ratna Sari Dewi; Ira Oktaviyani; Nia Ardiyanti; Vita Zahara Sitorus; Muhammad Azizi Syahputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to uncover the challenges faced by Mr. Jailani in starting and developing the "Bandrek Pak Kumis" UMKM and the strategies implemented to overcome them. The method used is qualitative with a case study approach, through in-depth interviews and direct observation of the business process. The results of the study indicate that limited capital, market competition, and marketing are the main obstacles. However, product innovation, utilization of social media, and building community relations are the keys to Mr. Jailani's success. The conclusion of this study emphasizes the importance of perseverance, creativity, and adaptation in facing the challenges of UMKM.